"90% of the time, it's not just weight": General practitioner and practice staff perspectives regarding the barriers and enablers to obesity guideline implementation. Issue 4 (July 2019) - Mazza, D.; McCarthy, E.; Carey, M.; Turner, L.; Harris, M.
Abstract: Objective: To identify the views of GPs and general practice staff regarding barriers and enablers to implementation of obesity guideline recommendations in general practice. Methods: Twenty general practitioners (GPs) and 18 practice staff from inner-eastern Melbourne, Australia, participated in semi-structured telephone interviews. The interview schedule was informed by the Theoretical Domains Framework (TDF). Interviews were audio-recorded, transcribed verbatim and underwent thematic analysis. Results: Participants lacked familiarity with and knowledge of the NHMRC obesity guidelines. Barriers and enablers were predominantly related to five theoretical domains: (1) environmental context and resources, (2) knowledge, (3) emotion, (4) beliefs about consequences, and (5) motivation and goals. Time pressures in consultations, costs for the patient, reluctance to add to patient burden particularly in those with comorbidities such as mental health issues, lack of awareness about services to refer patients to and GPs' fear of embarrassing patients and losing them were significant barriers. Enablers included having a strong doctor–patient relationship and a sense of responsibility to the patient to address weight. Conclusions: Obesity guidelines and policy makers need to better engage with issues of multimorbidity, socioeconomic disadvantage and workforce issues if recommendations are to be widely adopted in general practice. Tasksharing, teamwork and technology are potential solutions to some of the barriers. Patient perspectives and approaches to being able to overcome stigma and legitimise obesity management in primary care consultations could also assist.